2021
DOI: 10.35848/1882-0786/ac0481
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Bloch oscillations in acoustic waveguide arrays

Abstract: We designed a type of acoustic waveguide supported by spoof acoustic surface waves. The effective refractive index of acoustic waveguide can be effectively tuned by tailoring the waveguide width to control the propagation of spoof acoustic surface waves. Based on the advantage of the tunable refractive index, we construct a discrete waveguide array with transverse refractive index gradients to simulate the time evolution of the probability waves of electron in a tight-binding lattice under an external electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A comprehensive review on optical Bloch oscillations, Zener tunneling and related effects can be found in [21]. It is important to acknowledge that Bloch oscillations are a very generic effect and occur in a large number of physical systems such as atomic systems [22][23][24][25][26][27], lasers [28], coupled LC circuits [29], mechanical systems [30][31][32][33], plasmonic [34][35][36][37][38][39] or exciton-polariton systems [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on optical Bloch oscillations, Zener tunneling and related effects can be found in [21]. It is important to acknowledge that Bloch oscillations are a very generic effect and occur in a large number of physical systems such as atomic systems [22][23][24][25][26][27], lasers [28], coupled LC circuits [29], mechanical systems [30][31][32][33], plasmonic [34][35][36][37][38][39] or exciton-polariton systems [40][41][42].…”
Section: Introductionmentioning
confidence: 99%